Pengaruh Whistleblowing System, Efektivitas Pengendalian Internal dan Integritas Karyawan terhadap Kecendrungan Kecurangan (Fraud) pada Lpd Se-Kecamatan Selat Kabupaten Karangasem - Paramita, Ni Putu Eka Rahayu; Bayu Putra, Cokorda Gde; Ayu, Putu Cita (UNHI Press, 2025)
An action or deed carried out by an individual or a group intentionally which has a purpose or motive to gain personal benefit through the improper use of organizational resources is the notion of fraud. Until now cases of fraud and fraud against Village Credit Institutions (LPD) still occur, many Village Credit Institutions have also encountered various kinds of problems that have led to bankruptcy. From the research activities that have been carried out, the results state that there is a negative effect of whistleblowing on the tendency to act fraudulently. The effectiveness of internal control also has a negative influence on the tendency to act fraudulently. And employee integrity has a negative influence on fraudulent tendencies. In the future, it is hoped that all employees at the Village Credit Institution in Selat District are required to have the courage to disclose various acts of fraud. Because this will later be able to assist supervision in order to immediately handle and eradicate various existing fraudulent acts so as not to create losses for the Village Credit Institution.